Effect of reduction protocol of Pd catalysts on product distribution in furfural hydrogenation - Date, N. S.; Biradar, N. S.; Chikate, R. C.; Rode, C. V. (ChemistrySelect, 2017)
Single step conversion of furfural to ring hydrogenation and decarbonylation products, 2-methyltetrahydrofuran (2-MeTHF) and tetrahydrofuran (THF) in high selectivity was achieved by controlling the particle size of Pd/C catalyst. The particle size variation of Pd/C catalysts in the range of 3.8 to 22 nm could be achieved by employing different reducing agents. Of particular interest was the NaBH4 reduced catalyst (Pd-B/C), which gave the lowest crystallite size of 4.8 nm due to incorporation of B into the inner lattices of Pd-Pd. This phase was evidenced by a characteristic XRD peak of Pd-B at 2q=38.85 degrees as well as a shift of (111) peak (40.07 degrees) of Pd towards the lower value (39.8 degrees). As compared to formaldehyde reduced catalyst (Pd-F/C), Pd-B/C catalyst completely suppressed the formation of furfuryl alcohol to give > 65% selectivity to 2-MeTHF and THF. At 180 degrees C, almost equal distribution of side chain hydrogenation and ring opening products, 2-MF (45%) and PeDO (37 %), respectively, was observed while, higher temperature clearly favoured ring hydrogenation and decarbonylation reactions to give 2-MeTHF and THF.